Specific Detection of Pathological Three‐repeat Tau after Pretreatment with Potassium Permanganate and Oxalic Acid in PSP/CBD Brains - Uchihara, Toshiki (Brain Pathol, 2010)
Immunohistochemisty with RD3, a monoclonal antibody specific for three‐repeat (3R) tau, is sometimes hampered by diffuse neuronal staining on formalin‐fixed, paraffin‐embedded sections pretreated with formic acid and heating. Additional pretreatment with potassium permanganate followed by oxalic acid completely eliminated this diffuse RD3‐immunoreactivity (IR) in neurons. Furthermore, this additional pretreatment uniformly enhanced RD3‐IR, as well as RD4‐IR, a monoclonal antibody specific for four‐repeat (4R) tau, on pathological deposits with tau IR. This enhanced sensitivity and specificity may allow more reliable identification of 3R and 4R tau in pathological deposits, which may be variable dependent on disease and regions. Cerebral cortex and midbrain from 8 patients [5 progressive supranuclear palsy (PSP) and 3 corticobasal degeneration (CBD)] were screened for RD3‐ and RD4‐IR with this improved procedure. In addition to RD4‐positive structures found both in cerebral cortex and brainstem, RD3‐positive neurofibrillary tangles (NFTs) were also found in midbrain in 7 of these 8 cases but not in the cortex. Multi‐labeling study demonstrated that most of RD3‐negative neurons were positive for RD4. This reliable demonstration of pathological 3R tau deposits in the brainstem of PSP/CBD, so far presumably characterized by deposition of 4R tau, is useful to map tau‐positive lesions according to their biochemical composition.